Challenges of E-Learning During Covid-19 Pandemic: An Experience Of Educators And Students Of Faculty Of Medicine And Defence Health (FMDH), National Defence University Of Malaysia (NDUM) - Mohd Yusof, Yasmin Anum (Bangladesh Journal of Medical Science, 2021)
The COVID-19 pandemic has changed the medical teaching paradigm worldwide. Online classes and assessments have been introduced using many teaching platforms. Medical faculties in Malaysia faced many challenges in the past two years when most clinical teachings were halted. Students were also struggling to adapt to the new online learning versus traditional classroom settings. This paper describes the experience of educators of the faculty of medicine of NDUM. Bangladesh Journal of Medical Science Vol.20(5) 2021 p.175-177